Thomas Mann’s Novella “Death in Venice” in Intertext of Culture - S. T. Rzayeva (Научный диалог, 2018)
Autobiographical motives in the novella “Death in Venice” by German writer Thomas Mann are considered. The author and his family’s trip to Italy, the history of creation of the work and the relationship between personal experiences of Th. Mann, on the one hand, and the thoughts and feelings of the hero of the novel, on the other, are described. The memories of the writer’s wife Katia Mann about some of the travel experiences in Italy and about the people who have served as prototypes for the characters in the novel are presented that, among other things, confirms the autobiographical character of the work. Critical studies of the novel “Death in Venice,” which mainly had a laudable character, are considered. The influence of the work on the works of other writers is noted, among which there are the works of Wolfgang Copens, Max Frisch, Philip Roth, etc. It is shown that the novel “Death in Venice” formed the basis of opera and film and is one of the most famous works in the world. The phenomenon of spiritual kinship between two great representatives of German literature of the first half of the 20th century Thomas Mann and Hermann Hesse is considered, certain similarity of their works “Death in Venice” and “Klein and Wagner,” mainly in representation of images of their main characters is analyzed.